About the Date of the Crimean Gothia Creation - Aleksandr I. Aybabin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2018)
Introduction. Historians date the creation of the Crimean Gothia by 325 or the beginning of the 5th century, or the beginning of the 8th century.